Identifying online and Edmonton community based support groups for LGBTQ young adults with cancer - Tariq, Aqsa (My University, 2018)
The current study examined websites and brochures to determine and identify the emotional support networks that exist for young adult LGBTQ with cancer. Using content analyses, the researcher coded themes of support groups online and in the Edmonton community. Although no sources could be identified that were established specifically for young adult LGBTQ cancer survivors, the findings revealed 21 resources appropriate for young LGBTQ adults and/or young adults with cancer as described herein.
Presented on April 23, 2018 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: young adults; LGBTQ; cancer; support groups